PERAN SUSTAINABILITY REPORTING DALAM PENENTUAN KREDIT PERUSAHAAN - Sultan Rafli (Jurnal Akuntansi dan Bisnis, 2025)
Credit rating is a tool commonly used by investors to analyse the risk of a borrower. Nowadays, credit rating isn’t measured by financial metrics alone, but has been factoring in non-financial metrics such as company sustainability. This research employs a review of previous studies to explore the development of corporate sustainability’s role as a non-financial metric in determining corporate creditworthiness, based on global credit rating models such as S&P, Moody’s, Fitch, and so on. The findings indicate a positive relationship between corporate sustainability and credit ratings, where improvements in ESG scores and CSR activities are generally followed by higher credit ratings and lower default risk.